The Role of Nursing in Public Health: Strengthening Healthcare Systems for Better Access and Care - Qalbi, Ummul (Jurnal Perilaku Kesehatan Terpadu, 2024)
Malnutrition remains a persistent global health challenge with profound implications for individuals and communities. This study evaluates the role of nursing in addressing malnutrition and strengthening healthcare systems to improve accessibility and quality of care. Utilizing a mixed-methods approach, quantitative and qualitative data were collected from diverse populations, including children, adolescents, adults, and older individuals, to assess the prevalence of malnutrition and the effectiveness of nursing-led interventions. Findings indicate a concerning prevalence of stunting and wasting among children under five, underscoring the urgency of targeted nutrition-focused initiatives. Additionally, the study highlights the dual burden of malnutrition, where both undernutrition and overnutrition coexist across various age groups. Evidence from this research supports the effectiveness of nursing-led health promotion programs, including nutrition education, maternal and child health services, and food fortification initiatives, in reducing malnutrition-related morbidity. Nurses play a crucial role in identifying at-risk populations, implementing community-based nutrition programs, and advocating for policy changes that promote food security and sustainable healthcare interventions. Furthermore, nursing integration within interprofessional healthcare teams has been shown to enhance patient-centered care, increase vaccination rates, improve chronic disease management, and expand healthcare access through telehealth services. Despite the proven benefits of nursing-led interventions, challenges remain, including workforce shortages, healthcare disparities, and administrative constraints that hinder program implementation. Addressing these barriers requires strong policy support, workforce development, and investment in nursing education to ensure equitable access to high-quality nutrition and healthcare services. This study emphasizes the importance of evidence-based, context-specific nursing interventions in combating malnutrition and advancing public health. Future research should focus on the cost-effectiveness and long-term impact of these interventions to further optimize public health outcomes.